Implementation of Accelerated Stunting Reduction at the Biromaru Public Health Center, Sigi Regency - Sudirman, Sudirman; Rosnawati, Rosnawati; Afni, Nur; Yani, Ahmad; Syukran, Muhammad (Poltekita : Jurnal Ilmu Kesehatan, 2023)
This study aims to determine the implementation of stunting reduction policies at the Biromaru Public Health Center, Sigi Regency, a conceptual model using Edward III's theory from the aspects of Communication, Resources, Disposition, and Organizational Structure. The research method used is qualitative research, namely observation, in-depth interviews, and documentation. Based on the study results, it can be concluded that the stunting reduction policy implementation at the Biromaru Public Health Center in Sigi Regency has not run optimally. This is evident from the inadequate implementation of the aspects of Communication, Resources, Disposition, and Organizational Structure. Several obstacles hinder the implementation of stunting reduction policies. The resources at the Biromaru Health Center in Sigi Regency are lacking, especially in terms of facilities like scales and height measuring devices. Not all posyandu centers receive these resources due to budget limitations, which vary by village. This affects the optimal implementation of the policy. Regarding the Organizational Structure and Standard Operating Procedure (SOP), while they have not yet been established, all officers maintain a good working relationship, as confirmed through interviews showing their collaborative efforts in the program.